Health shocks adversely impact participation in the labour force in a working age population: a longitudinal analysis - Kristie N. Carter; Fiona Imlach Gunasekara; Tony Blakely; Ken Richardson (Elsevier, 2013)
Abstract Background : It is well understood that health affects labour force participation (LFP). However, much of the published research has been on older (retiring age) populations and using subjective health measures. This paper aims to assess the impact of an objective measure of 'health shock' (cancer registration or hospitalisation) on LFP in a working age population using longitudinal panel study data and fixed effect regression analyses. Methods : Seven waves of data from 2002-09 from the longitudinal Survey of Family, Income and Employment (SoFIE) were used, including working aged individuals who consented to have their survey information linked to health records (n=6,780). Fixed effect conditional logistic regression was used to model the impact of health shocks (hospitalisation or cancer registration) in the previous year on labour force participation at date of annual interview. Models were stratified by gender, age group (25-39 years, 40-54 years) and gender by age group. Results : A health shock was associated with a significantly increased risk of subsequent non‐participation in the labour force (odds ratio 1.54, 95%CI 1.30-1.82). Although interactions of age, sex and age by sex with health shock were not statistically significant, the association was largest in younger men and women. Conclusion : Using an objective measure of health, we have shown that a health shock adversely affects subsequent labour force participation. There are a number of policy and practice implications relating to support for working age people who have hospitalisations.